Investigation of h2s donor treatment on neutrophil extracellular traps in experimental colitis - Török Szilvia; Almási Nikoletta; Valkusz Zsuzsanna; Pósa Anikó; Varga Csaba; Kupai Krisztina (2021)
Inflammatory bowel diseases (IBD) are chronic, immune-mediated disorders, which affect the gastrointestinal tract with intermittent ulceration. It is increasingly clear that neutrophil extracellular traps (NETs) seem to have a role in IBD; however, the associated pathogenesis is still not known. Furthermore, several conventional therapies are available against IBD, although these might have side effects. Our current study aimed to investigate the effects of hydrogen sulfide (H2S) treatment on NETs formation and on the expression of inflammatory mediators in experimental rat colitis. To model IBD, 2,4,6-trinitrobenzenesulfonic acid (TNBS) was administered intracolonically (i.c.) to Wistar–Harlan male rats. Animals were treated (2 times/day) with H2S donor Lawesson’s reagent per os. Our results showed that H2S treatment significantly decreased the extent of colonic lesions. Furthermore, the expression of members of NETs formation: peptidyl arginine deiminase 4 (PAD4), citrullinated histone H3 (citH3), myeloperoxidase (MPO) and inflammatory regulators, such as nuclear transcription factor-kappa B (NF-κB) and high-mobility group box 1 (HMGB1) were reduced in H2S treated group compared to TNBS. Additionally, H2S donor administration elevated the expression of ubiquitin C-terminal hydroxylase L1 (UCHL-1), a potential anti-inflammatory mediator. Taken together, our results showed that H2S may exert anti-inflammatory effect through the inhibition of NETs formation, which suggests a new therapeutic approach against IBD. © 2021 by the authors. Licensee MDPI, Basel, Switzerland.
Keywords: Klinikai orvostan